Electro discharge machining performance of cryogenic heat treated copper electrode - Apak, Savas; Ay, Mustafa (Walter de Gruyter Gmbh, 2024)
In this study, the EDM machining performance of a cryogenic heat treated copper electrode was investigated. Within the scope of the study, electrodes selected from copper material were subjected to cryogenic heat treatment with a cycle between [room temperature/ - 184 degrees C/room temperature]. In the experimental design, the electrode material was changed at two levels: copper electrode (Cu) and cryogenic copper electrode (CCu). Controllable machine parameters, peak current (Ip), active pulse duration (Ton), pulse gap duration (Toff) and gap voltage (Vg) were changed at three levels. The effects of these parameters on outputs such as recast layer thickness (RLT), material removal rate (MRR), electrode wear rate (EWR) and taper angle (TA), which are taken into consideration in determining the processing quality after EDM machining experiments, were taken into account. A total of 18 experiments were carried out on Ti-6Al-4V (Titanium alloy) workpiece with copper electrode. Lower YKTK with combinations of EDM process parameters such as cryogenic copper electrode (CCu), 4 A peak current (Ip), 110 mu s active pulse duration (Ton), 72 mu s pulse gap time (Toff) and 6 V gap voltage (Vg), It was observed that EWR and TA and higher MRR were obtained.
Keywords: cryogenic heat treatment; EDM; Ti-6Al-4V